Big data analytics enabled by feature extraction based on partial independence - Ke, Qiao; Zhang, Jiangshe; Song, Houbing; Wan, Yan (Neurocomputing (Amsterdam), 2018)
Complex cells in primary visual cortex (V1) selectively respond to bars and edges at a particular location and orientation. Namely, they are relatively invariant to the phase as well as selective to the frequency and orientation emerging from natural images that are analogous to the characteristics of complex cells in V1 with the energy function of receptive fields (RFs) from tuning curve test with sinusoidal function in our related jobs. In this paper, we propose a feature learning algorithm based on the overcomplete AISA to apply on big data in parallel computing. In order to demonstrate the effectiveness of the overcomplete AISA features in the classification task, two feature representation architectures are evolved into the partial independent signal bases and partial independent factorial representation, respectively. Experiments on four datasets (Coil20, Extended YaleB, USPS, PIE), acquired conjunction with two classification architectures based on the overcomplete AISA features, show that the classification accuracy is mostly higher than those obtained from the other ICA related features and two other sparse representation features with a small number of training samples via nearest neighbor (NN) classification method.